Legitimating Business Improvement Districts in Johannesburg: A discursive perspective on urban regeneration and policy transfer - (:unkn) unknown (My University, 2012)
This article considers the transfer of the Business Improvement District concept to South Africa from a discursive perspective. It examines the ways in which the private sector (property and business owners) has justified the adoption of the model and how it has moulded the concept to Johannesburg's inner city. Drawing on critical discourse analysis, this paper focuses on legitimation strategies, locating them within broader social practices and power relations within the framework of urban revitalization policies implemented after the democratic transition. By focusing on legitimation strategies, and more particularly on their linguistic and semiotic aspects at the micro level, the article shows how the analysis of language use, particularly through a socio-cognitive approach (Van Dijk, 2009), can contribute to uncovering the opinions, attitudes, ideologies, norms and values of social actors. It can also offer insights into a local reinterpretation of a globally circulating model. The comparative analysis of two case studies highlights changing assumptions and attitudes, at least in local rhetoric, and demonstrates how the imported model has been reshaped not only by different discourses associated with various social practices but also by changing policy demands. By considering discourse as an instrument of the social construction of reality as well as an instrument of power and control, the chosen approach also underlines the way in which inequalities are reproduced and maintained in Johannesburg.
Keywords: African Research